2013
DOI: 10.1519/jsc.0b013e31829bd7c5
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Muscle Architecture Comparisons Between Starters and Nonstarters in National Collegiate Athletic Association Division I Women's Soccer

Abstract: This study compared performance and muscle architecture (MA) changes in starters (S) and nonstarters (NS) during a National Collegiate Athletic Association Division I women's soccer season. Twenty-eight women (19.9 ± 1.1 years; 1.71 ± 0.08 m; 64.7 ± 6.4 kg) were monitored for vertical jump power (VJP), repeated line drills (LDs), 3-dimensional multiple object tracking (3D-MOT), and reaction time (RT) at preseason, midseason, and postseason. Muscle architecture changes using ultrasonography were assessed at pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 41 publications
(67 reference statements)
4
49
2
2
Order By: Relevance
“…For example, previous investigations in these populations have reported EI ICC values calculated either between days (i.e., test-retest) or across differentsized ROIs (Caresio et al 2014) ranging from 0.540 to 0.760 for the medial gastrocnemius (Caresio et al 2014;Rosenberg et al 2014), 0.720 to 0.920 for the biceps brachii (Caresio et al 2014;Chen et al 2012;Radaelli et al 2012), 0.571 to 0.910 for the rectus femoris (Caresio et al 2014;Jajtner et al 2013;Strasser et al 2013) and 0.623 to 0.980 for the vastus lateralis muscles (Caresio et al 2014;Jajtner et al 2013;Strasser et al 2013, Wells et al 2014). Although we are aware of no previous reliability studies to date that have examined EI for the hamstring muscles, the present study's ICC findings of 0.715-0.917 were comparable to those previously reported for EI for the biceps brachii and rectus femoris (Caresio et al 2014;Chen et al 2012;Radaelli et al 2012;Strasser et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous investigations in these populations have reported EI ICC values calculated either between days (i.e., test-retest) or across differentsized ROIs (Caresio et al 2014) ranging from 0.540 to 0.760 for the medial gastrocnemius (Caresio et al 2014;Rosenberg et al 2014), 0.720 to 0.920 for the biceps brachii (Caresio et al 2014;Chen et al 2012;Radaelli et al 2012), 0.571 to 0.910 for the rectus femoris (Caresio et al 2014;Jajtner et al 2013;Strasser et al 2013) and 0.623 to 0.980 for the vastus lateralis muscles (Caresio et al 2014;Jajtner et al 2013;Strasser et al 2013, Wells et al 2014). Although we are aware of no previous reliability studies to date that have examined EI for the hamstring muscles, the present study's ICC findings of 0.715-0.917 were comparable to those previously reported for EI for the biceps brachii and rectus femoris (Caresio et al 2014;Chen et al 2012;Radaelli et al 2012;Strasser et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous research studies examining the reliability of US to measure muscle architecture of the locomotor-related lower body muscles such as the quadriceps and plantar flexors (Jajtner et al 2013;Melvin et al 2014;Rosenberg et al 2014;Scanlon et al 2014;Wells et al 2014), interestingly, we are aware of only a few studies to date that have examined the reliability of US to measure muscle architecture of the hamstring muscle group (i.e., biceps femoris [BF], semitendinosus [ST], semimembranosus [SM]) (Chleboun et al 2001;Kellis et al 2009;Timmins et al 2014). Specifically, Chleboun et al (2001), Kellis et al (2009) andTimmins et al (2014) reported that US was a valid and reliable assessment tool for examining MT, fascicle length and/or pennation angle of the BF and ST.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ultrasound has been used to evaluate muscle characteristics in athletes (8, 15, 23). Measurements of muscle cross sectional area (mCSA) and echo intensity (EI) can be used to assess muscle size and quality, respectively (2).…”
Section: Introductionmentioning
confidence: 99%
“…Le protocole d'étirements consistait en deux répétitions de 10 secondes d'étirements statiques de 5 groupes musculaires les plus sollicités durant l'exercice footballistique [19,20] : fessiers, adducteurs, quadriceps, ischiojambiers, triceps. Ces exercices étaient à l'image de ceux habituellement réalisés par les footballeurs de ce club en fin d'entraînement.…”
Section: Protocole D'étirementsunclassified
“…Il y a eu 20 Concernant les circonstances de survenue des blessures, 8 se sont produites pendant l'entraînement : 4 dans chaque groupe. L'incidence des blessures à l'entraînement pour 1000 heures de pratique était de 1,7 pour GE contre 2,6 pour GC avec un RR de 1 entre les deux groupes (IC 95 % 0,28-3,47).…”
Section: Incidence Des Blessuresunclassified